How can we make GPS tracking studies more open, reproducible, and collaborative? A vision for the OpenGPS platform - Milad Malekzadeh; Hui Jeong Ha; Katarzyna Sila-Nowicka; Vanessa Brum-Bastos; Jinhyung Lee; Urška Demšar; Jed A. Long (Data in Brief)
This paper introduces OpenGPS, a platform envisioned for the archiving and processing of human mobility GPS data. The OpenGPS addresses the need for a centralized, privacy-preserving system that securely stores, shares, and analyzes GPS tracking datasets. The platform is envisioned to develop in three phases. Phase I focuses on collecting metadata from existing GPS tracking studies worldwide, providing a foundation for future research. Phase II involves archiving GPS data with standardized formats and robust privacy safeguards, ensuring data is accessible while protecting individual privacy. Phase III integrates advanced analytical tools and workflows directly into the platform, enabling efficient analysis and fostering collaboration among researchers. The OpenGPS aims to overcome the limitations of current human mobility studies by offering a standardized repository that enhances reproducibility and openness in research. By facilitating the sharing of data and methodologies, the OpenGPS will promote new insights and innovations in human mobility research. This platform is poised to become a critical resource for the scientific community, bridging gaps in data availability, and enabling comprehensive meta-analyses across different geographical and temporal scales. Through OpenGPS, researchers can collaborate more effectively, share resources, and advance the understanding of human mobility patterns globally.